AKUNTABILITAS PADA BAITUL MAAL WAT TAMWIL DITINJAU DARI PERSPEKTIF SHARI'ATE ENTERPRISE THEORY - Siti Amerieska; Gugus Irianto; Didied P. Affandy (Jurnal Ekonomi & Keuangan Islam, 2012)
Accountability is one of the most important concepts in business and organizations. Understanding accountability itself became important for the actor who play the operational and performance to realize accountability in business and organizations. But accountability now has “less” interpretative; cause without aware with all stakeholders. Organization just think the most important contribute given by direct stakeholder only. SET (Shari‘ate Enterprise Theory) give the alternative solution about dimension of relationship on accountability. The alternative dimension relation first of all is dimension relation people with God. Second relation dimension is between people with people that have two categories direct and indirect stakeholder. And the third dimension is relation people with environmental, people with God. Reality accountability in BMT, have effort to realize accountability with all stakeholder. But in the realty still have superior accountability relation, which in categories dimension between people with people.